The development of approximation theory and some proposed applications - Saad Al-Muhja, Malik; Misiran, Masnita; Omar, Zurni (International Journal of Engineering and Technology, 2019)
In this survey article, we review the early history of approximation theorem that was introduced by Weierstrass in the late 18th century, together with its extension works. We also propose some applicable scenarios that best fit this theory. Such applications include the kinetics conditions related to manual and automatic vehicle transmission by using convex function, and the theory of calculating deviations of eyeâ€™s layers (normal vision, hyperopia and myopia) in some patients by using monotone function.Â Â Â Â